Ultrasonic-Assisted Removal of Eriochrome Black T onto Vermicompost: Characterization, Isotherm and Kinetic Modelling - Zeynep CİGEROGLU (Turkish Chemical Society, 2021)
Recently, utilization of biological adsorbents plays an important role in the removal of toxic dyes such as Eriochrome Black T (EBT) azo-dye as they are considered as being produced from natural renewable source, easy availability, low cost, and being environmentally friendly. In this study, vermicompost (VC) was utilized to remove Eriochrome Black T (EBT) azo-dye from aqueous solution along ultrasonic ultrasonic-assisted adsorption. The parameters such as pH, adsorbent amount, operating time, and initial EBT concentration were investigated. The highest adsorption capacity was obtained as 50.64 (mg-EBT g-1-VC) at the pH of value of 2 after 2 minutes of ultrasonic adsorption. Pseudo first order kinetic model fitted very well with the experimental data (R2=0.9824). The determination coefficient of Temkin isotherm model (R2=0.8659) revealed that suggested model was compatible to experimental results. The results suggested that ultrasonic assisted adsorption of EBT onto VC could be cost- and time-efficient. Besides, the Scanning Electron Microscopy (SEM) analysis of adsorbent identified the surface structure morphology of VC. Moreover, functional groups of VC were detected after and before the ultrasonic-assisted adsorption by using Fourier Transform Infrared Spectroscopy (FTIR). Thus, interaction mechanism between VC and EBT were determined.